Ethnomusicology of the individual - Pettan, Svanibor (Muzikološki zbornik, 2018)
The article presents the case of a creative Indian classical music artist respectful of tradition and open towards experimentation. Based on the interviews and participant observation, it presents the artist's views and his four innovative musical instruments. The article fits in the theoretical frame of ethnomusicology of the individual.
Keywords: Balaji, Vishnuchittan; etnomuzikologija; hindustanska glasba; indijska klasična glasba; indijski glasbeniki; inovativnost; tradicija; viola; violina